Vibrational spectroscopy reveals the initial steps of biological hydrogen evolution. Issue 11 (22nd July 2016) - Katz, S.; Noth, J.; Horch, M.; Shafaat, H. S.; Happe, T.; Hildebrandt, P.; Zebger, I.
Abstract : Low temperature resonance Raman spectroscopy reveals the initial, transient H-cluster intermediate during biological hydrogen production by [FeFe]-hydrogenase. Abstract : [FeFe] hydrogenases are biocatalytic model systems for the exploitation and investigation of catalytic hydrogen evolution. Here, we used vibrational spectroscopic techniques to characterize, in detail, redox transformations of the [FeFe] and [4Fe4S] sub-sites of the catalytic centre (H-cluster) in a monomeric [FeFe] hydrogenase. Through the application of low-temperature resonance Raman spectroscopy, we discovered a novel metastable intermediate that is characterized by an oxidized [Fe I Fe II ] centre and a reduced [4Fe4S] 1+ cluster. Based on this unusual configuration, this species is assigned to the first, deprotonated H-cluster intermediate of the [FeFe] hydrogenase catalytic cycle. Providing insights into the sequence of initial reaction steps, the identification of this species represents a key finding towards the mechanistic understanding of biological hydrogen evolution.